ClearT immersion optical clearing method for intact 3D spheroids imaging through confocal laser scanning microscopy - Costa, Elisabete Cristina da Rocha (2018)
Spheroids are 3D in vitro platforms that fill the gap between the 2D cell cultures and animal models on the therapeutics development pipeline. Yet, the methods and equipment used in the in vitro assays are optimized for the analysis of cells cultured as monolayers. For instance, confocal laser scanning microscopy (CLSM) does not allow the observation of thick intact spheroids due to light penetration issues. To overcome this limitation, spheroids treatment with clearing agents started to be explored. Herein, we demonstrate for the first time the application of ClearT clearing method for the imaging of propidium iodide (PI) stained spheroids by CLSM. The results demonstrate that the ClearT is a reversible clearing method that does not influence the structure of the spheroid and significantly improved the PI signal penetration depth in about 43%. Additionally, ClearT also enhanced the cells imaging within the spheroid by increasing the cross-penetration depth in 46.6% at 100 µm of depth. Overall, the results show that ClearT method may allow the improvement of the CLSM accuracy on the evaluation of the cellular death within spheroids prompted by therapeutics.